Experimental Performance and Auto-Regressive with eXogenous Input (ARX) Modelling of an Anti-UV Polycarbonate Sheet-covered Solar Dryer Equipped with a Control System for Drying Para Rubber Sheets - Aumporn, Orawan; Pankaew, Prasan; chanpen, Nattawut; Janjai, Serm (Journal of Renewable Energy and Smart Grid Technology, 2021)
This paper presents the experimental performance and ARX modelling of an anti-UV polycarbonate sheet-covered solar dryer equipped with a control system for drying para rubber sheets. The dryer was built at Silpakorn University (13.82ºN, 100.04ºE), Nakhon Pathom, Thailand. This dryer comprises a roof structure covered by anti-UV polycarbonate sheets, shelves for hanging the rubber sheets, concrete floor, ventilation system and drying control system. The control system comprises temperature and relative humidity sensors and an on-off controller of the ventilating fans. The dryer is a medium size of a large-scale greenhouse type which has a length of 12.4 m, a width of 8.0 m and a height of 3.5 m and it can be used to dry 500 para rubber sheets, each of which has a dimension of approximately 0.46 m × 0.90 m × 0.005 m. The experimental results revealed that the moisture content of the sheets can be reduced from 30% w.b. to the final value of 1% w.b. in 3 days and the control system functioned as it was designed. In addition, the polycarbonate sheets can protect para rubber sheets from UV solar radiation and high quality dried rubber sheets are obtained. Based on the drying experiments, the dryer was modelled using the ARX approach. It was found that the model predicted well moisture content of the rubber sheets dried in this dryer.